Impact of Digital Marketing Strategies on the Entrepreneurial Orientations of Jordan's Commercial Banks (Marketing i Menedžment Innovacij)
Technology finance has an increasingly significant impact on the state of the financial industry around the world, including Jordan. Digital marketing has the potential to improve the efficiency, creativity and value of financial services, which can contribute to the resilience and prosperity of customers. This research aims to determine digital marketing strategies (DMSs) and their impact on the entrepreneurial orientation (EO) of Jordan's commercial banks. To realize the dimensions of the digital marketing strategy. The study answers the main question addressed by this research, including whether there was a correlation and impact of the digital marketing strategy on the entrepreneurial orientation of commercial banks. The method uses a basic type with a quantitative, nonexperimentalapproach. Essential information obtained through the questionnaire was organized for this purpose and distributed to a sample of 137 staff at various levels. Descriptive and analytical statistical methods have been adopted, including computational media and standard deviations, and the correlations between variables and tests (t) have been used. All the variables have α (0.823 ~ 0.989); to ascertain the stability of the search tool, the value (F) achieved (241.359). The results reveal various perspectives on key business aspects and show that the correlation factor (R=.926) indicates that digital marketing affects entrepreneurial orientation. The results of this study explain the structural impact of the digital marketing strategy (targeting strategy, attack strategy, and proactive strategy) on the entrepreneurial orientation (proactive risk tolerance and creative and innovation) of Jordanian commercial banks. Thus, these tools are potentially effective and should be adopted by Jordanian commercial banks to improve existing strategies through investments in technology, data analysis and staff training.